Det utvidgade klassrummet – språkundervisning på distans - Karlsson, Johanna ; 0009-0005-9050-4070 (Lunds universitets pedagogiska utvecklingskonferens 2017, Lund, Sweden, 2017-11-23 - 2017-11-23, 2018)
Abstract The sociocultural theory, the idea that we learn in interaction with others, has had an immense impact on the field of education. For the past 20 years, the theory has gained momentum within the field of online education and inspired a group of researchers at the University of Alberta (Garrison, Anderson & Archer 2000) to design a conceptual framework and an online learning model of the already existing idea Community of Inquiry. The model consists of three elements, all of which are pointed out as crucial prerequisites for a successful online learning environment: social presence, teaching presence and cognitive presence. This study examines how the courses in Swedish at UCLA were re-designed when evolving into blended synchronous language courses, and what specific measures were taken to meet the need for social presence and teaching presence. Key findings include 1) the need for visual and auditory presence to feel as part of the group, 2) the importance of carefully selecting technologies for active learning, and 3) the importance of pedagogical adaptation in an online classroom.